Digital Organisational Culture: Capturing Local Banking in Digital Transformation - Rachman Wintarto; Meiliani Meiliani; Angelina Carolin (Universitas Pendidikan Ganesha, 2023)
Digital transformation in banking is a must and related to the culture in an organization to serve customers using digital technology to transform the internal processes of the business. Therefore, the purpose of this study is to analyze the process of digital transformation and the role of digital organizational culture in digital transformation in local banking. The sample of this study is employees who work at Bank Bengkulu (Bank of Bengkulu) which is a local government-owned bank. The research was conducted with a qualitative approach using open-ended questions with the e-survey questionnaire method. The collected data are analyzed using thematic analysis techniques. Research findings show that micro themes of digital transformation, such as outside-in, cross-work collaboration, work creativity, and agile leadership, are still not significantly developed at Bank Bengkulu. In addition, cultural behavior, digitalization capabilities, digitization skills, IT infrastructure, and business processes are also still weak. Some technology programs are still in the early stages of development and progress is slow. In conclusion, this study illustrates that digital transformation and digital organizational culture are still not significantly developed at Bank Bengkulu. Constraints such as inadequate human resource skills, weak IT infrastructure, and lack of responsiveness in the face of change need to be considered. The implication of the results of this study is the importance of attention to digital skills development, IT infrastructure improvement, and organizational culture change to achieve successful digital transformation at Bank Bengkulu.